Three new species of Leptoceridae Leach 1815 (Insecta: Trichoptera) from Shan State, Myanmar - Laudee, Pongsak; Malicky, Hans (Zootaxa, 2016)
Three new species of Leptoceridae, including Ceraclea satasookae n. sp., Setodes siribumrungsukhai n. sp., and S. salweenensis n. sp. are described and figured from Shan State, Myanmar. Twenty-two species of Leptoceridae were found and 21 of them are new records to the country.